THE USE OF ECOTOURISM FOR THE HEALTH OF STUDENTS - Irmatov Shavkat Anvarovich; Ashurova Navruzakhon Ergashalievna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
The following areas of ecotourism can be used to improve the health of students: recreational ecotourism, educational, sightseeing, sports, combined, etc. Carrying out several organizational measures (training of competent specialists in the field of physical recreation, development of various ecological tours of sports, and recreation orientation will contribute to the intensification of ecotourism development.